Anti-Radiation Damage Performance of Fullerene Ethanolamine - Li, Qun-Ling; Zhong, Zhi-Jing; Lin, Tao; Lin, Jin-Xian (Asian Journal of Chemistry, 2014)
Water soluble fullerene ethanolamine derivative was synthesized by adding fullerene (C60) into the ethanolamine under nitrogen atmosphere protection. Its molecular structure was characterized by FTIR and ESI-MS. Hydroxyl radicals were generated by adding ethanol solution and nitronyl nitroxide radicals were generated by adding 4-hydroxy-2,2,6,6-tetramethyl piperidine solution. With irradiation of g-ray, scavenging radicals efficiency of fullerene ethanolamine derivative reached to 49.2 %; with irradiation of fast neutron, fullerene ethanolamine derivative showed excellent scavenging radicals efficiency compared with other materials in experiments, which was decreased first and then increased and attained 65 % at most. The results reveal that no matter irradiation by g-rays or high-energy neutrons, fullerene ethanolamine derivative presentes favorable scavenging radicals efficiency and may be used as a affective protectant for two irradiations.